Social representation on deafness: an integrative review - Guimarães, Valéria Maria Azevedo (2022)
The present study aimed to carry out an integrative review of the literature regarding scientific studies involving social representation and deafness. For this, a search was carried out in the databases SciELO.org, PePSIC, LILACS, PsycINFO (APA) and Scopus (Elsevier), through the platform Periodicals CAPES, in September 2020. The descriptors were: representation social, deaf, deaf and hearing impaired, in Portuguese, English and Spanish. Eleven articles were analyzed with abouth the deaf, and hearing populations. In the articles with deaf people, themes about identity, culture and rights as citizens are observed to resolve and modify stereotypes about deafness. Surveys with listeners were carried out with family members and society in general, highlighting representations based on negative stereotypes and limiting aspects. Furthermore, new scientific productions are suggested that give continuity to the theory of social representations associated with other aspects that involve deafness and have the deaf community as a sample.